Antimicrobial resistance dissemination associated with intensive animal production practices in Argentina: A systematic review and meta-analysis - Prack McCormick, Barbara; Quiroga, María P.; Alvarez, Veronica E.; Centrón, Daniela; Tittonell, Pablo Adrian (Elsevier, 2023)
Abuse and misuse of antimicrobial agents has accelerated the spread of antimicrobial-resistant bacteria. The association between antimicrobial-resistant infections in humans and antimicrobial use in agriculture is complex, but well-documented. This study provides a systematic review and meta-analysis of the dissemination of antimicrobial resistance (AMR) to antimicrobials defined as critically important by the WHO, in swine, chicken, and cattle from intensive and extensive production systems in Argentina. We conducted searches in electronic databases (MEDLINE-PubMed, Web of Science, SciELO, the National System of Digital Repositories from Argentina) as well as in the gray literature. Inclusion criteria were epidemiological studies on AMR in the main food-transmitted bacteria, Salmonella spp., Campylobacter spp., Escherichia coli and Enterococcus spp., and mastitis-causing bacteria, isolated from swine, chicken, dairy and beef cattle from Argentina. This study gives evidence for supporting the hypothesis that AMR of common food-transmitted bacteria in Argentina is reaching alarming levels. Meta-analyses followed by subgroup analyses confirmed the association between the prevalence of AMR and (a) animal species (p<0.01) for streptomycin, ampicillin and tetracycline or (b) the animal production system (p<0.05) for streptomycin, cefotaxime, nalidixic acid, ampicillin and tetracycline. Moreover, swine (0.47 [0.29; 0.66]) and intensive production (0.62 [0.34; 0.83]) showed the highest pooled prevalence of multidrug resistance while dairy (0.056 [0.003; 0.524]) and extensive production (0.107 [0.043; 0.240]) showed the lowest. A research gap regarding beef-cattle from feedlot was identified. Finally, there is an urgent need for political measures meant to coordinate and harmonize AMR surveillance and regulate antimicrobial use in animal production.